The importance of Bucomaxillofacial Physiotherapy for Minor Oral Surgery (Research, Society and Development, 2021)
Minor oral surgery is a subspecialty of maxillofacial surgery, being responsible for surgical procedures related to bones, teeth gums and cheeks. It involves the diagnosis, treatment and monitoring of tooth extractions, minor injuries and trauma in the mouth, jaw and surrounding regions. (Pallota, 2020). Diagnosis is performed by the dental surgeon and is eminently clinical through intra and extra- oral physical examination. Postoperative pain treatment must be done and meet the individual needs of each patient, respecting their pain threshold, as well as other aspects inherent to the patient ( Rocha et al, 2007). The objective of this article is to verify, through a surgery of the literature, the incidence of minor oral sugery in the last fifteen years and the last fifteen years ( 2005 a 2021), carried out by consulting academic quality reading material. By observing the results obtained, this article enable the analysis of maxillofacial physioterapy, which has as its main objective the rehabilitation of the patient’s facial structures with techniques, exercises and specialized procedures for each condition.